Clinico-etiological profile of acute liver failure in children in a tertiary care hospital of northernmost India - Wani, Khurshid; Wani, Jawad Nazir; Zaman, Bashir U.; Mir , Naseer Yousuf (International Journal of Contemporary Pediatrics, 2024)
Background: Acute liver failure is a life-threatening condition with sudden onset liver injury, decreased liver functions, hepatic encephalopathy, and coagulopathy in patients without preexisting liver disease. The objective of this study was to find out the clinical and etiological factors of acute liver failure in children. Methods: This study was a hospital based prospective observational study conducted from November 2017 to October 2019 at Pediatric Intensive Care Unit (PICU) of Postgraduate Department of Pediatrics, Government Medical College Srinagar, Kashmir. Fifty-one consecutive patients of ALF in the age group of 1 to 18 years were included in this study. Results: The most common clinical presentation in our study was jaundice which was present in all cases followed by anorexia (90.2%), vomiting (84.3%), fever (76.5%) and abdominal pain (64.7%). HE was present at admission in 54.9% cases and exaggerated DTR’s was present in 49% cases. Of the other clinical manifestations, bleeding was present in 49% cases, ascites in 33.3% cases and edema in 5.9% cases. Infections (76.5%) were the most common cause of ALF in children followed by indeterminate (9.8%), autoimmune (5.9%), drug induced (3.9%), Wilson’s disease (2%) and HLH (2%). In infectious etiology, the most common cause was Hepatitis A (66.7%) followed by Enteric fever (7.8%) and Hepatitis E (2%). Conclusions: The most common clinical manifestation of ALF in children is Jandice. Hepatitis A is the most common cause of ALF in children.